2020
DOI: 10.1158/2159-8290.cd-20-0304
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Directs Hepatocytes to Recruit MDSCs and Promote Cholangiocarcinoma

Abstract: Gut dysbiosis is commonly observed in patients with cirrhosis and chronic gastrointestinal disorders, however, its effect on anti-tumor immunity in the liver is largely unknown. Here we studied how the gut microbiome affects anti-tumor immunity in cholangiocarcinoma. Primary sclerosing cholangitis (PSC) or colitis, two known risk factors for cholangiocarcinoma, which promote tumor development in mice caused an accumulation of CXCR2 + polymorphonuclear myeloid-derived suppressor cells (PMN-MDSC). A decrease in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 86 publications
2
109
0
Order By: Relevance
“…Hepatocytes secreted CXCL1, a chemokine responsible for PMN-MDSC recruitment, upon interaction with Gram-negative bacteria via their TLR4. Intrahepatic cholangiocarcinoma patient data also support the role of bacteria in tumor progression, which shows that those with lower expression of TLR4 have longer overall survival [127]. Gut dysbiosis that occurs after exposure to the carcinogenic compound 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) also leads to an accumulation of MDSCs in the peritoneal cavity of mice [128].…”
Section: Mdscs and Microbiomementioning
confidence: 88%
“…Hepatocytes secreted CXCL1, a chemokine responsible for PMN-MDSC recruitment, upon interaction with Gram-negative bacteria via their TLR4. Intrahepatic cholangiocarcinoma patient data also support the role of bacteria in tumor progression, which shows that those with lower expression of TLR4 have longer overall survival [127]. Gut dysbiosis that occurs after exposure to the carcinogenic compound 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) also leads to an accumulation of MDSCs in the peritoneal cavity of mice [128].…”
Section: Mdscs and Microbiomementioning
confidence: 88%
“…The murine CCA cell lines SB1 24 and LD-1, as well as the human CAA cell line EGI-1, 25 were used in this study. LD-1 26 was established in our laboratory and is derived from a mouse after hydrodynamic injection with AKT and YAP plasmids. WES data from LD-1 as well as SB1 will be provided upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Although the exact mechanisms remain unclear, several studies could serve as valuable references for us to speculate how gut microbiome promoted the accumulation of MDSC. Recently, Zhang et al 133 demonstrated that in the mice models of Cholangiocarcinoma, an impairment of gut barrier could result in the migration of gut-derived bacteria to the liver, which induced CXCL1 secretion from hepatocytes through TLR4 pathway and subsequently caused PMN-MDSC accumulation. This means that the gut microbiota could serve as pathogen-associated molecular patterns to interact with the pattern-related receptors and create an immunosuppressive environment in the target organ through induction of MDSC-recruiting cytokines and chemokines.…”
Section: The Interactions Between Mdsc and Other Components In The Tmementioning
confidence: 99%